Herpes Viruses: An Appraisal, Clinical Reports and Insights - Louis Z.G. Touyz; Leonardo M. Nassani (Journal of Orofacial Research, 2021)
Herpes viruses occur ubiquitously among humans across the globe. This appraisal describes the molecular structure of Herpes viruses with the known types of Human Herpes Virus (Types 1-8), deconstructs, and describes the pathogenesis and clinical presentations of primary and recurrent Herpes oral infection. Illustrated here are Human Herpes Simplex Virus-1 (HHSV-1) as a primary oral herpes infection, a recurrent Herpes labialis, HHSV-1 with blood infusion, a post-op Herpes, and a radiograph of rapidly progressive periodontitis associated with Herpes. There are no strict protocols of management, and suggested treatments of oral manifestations are discussed. Therapeutic drugs available are listed and a costing for them in North America is indicated. Therapy can treat the symptoms and manifestations, but no vaccine or reliable prophylactic inoculations exists against the Human Herpes Viruses.